(untitled) (Italian Journal of Public Health, 2007)
Italian university students were investigated for: sources of information about HIV, knowledge of HIV risk behaviours, as well as sexual behaviours and condom use. A self completed anonymous questionnaire was administered to 430 university students in Campobasso, Italy (mean age 23,1; males 35,8%). Although TV, radio and the printed press were the most common sources of HIV information (>60% of respondents), most respondents preferred to receive information from physicians or resource centres (50 and 51%). Most students (>97%) were aware that specific sexual behaviours (unprotected vaginal or anal intercourse) and sharing of needles with illegal injecting drug users could transmit HIV. Most students (>50%) did not regularly use condoms (despite understanding their protective effect), and continued to engage in behaviours considered risky. Males were significantly more likely than females to engage in vaginal sex (84 vs. 67%) or anal sex (37 vs. 13%) with both regular and casual partners. Although knowledge of HIV in itself is not enough to produce behaviour change, increases in students’ levels of knowledge may be useful.